PERANCANGAN SISTEM INFORMASI CATATAN KESEHATAN IBU HAMIL DAN IBU BERSALIN BERBASIS SMS NOTIFIKASI - Noor Latifah (Universitas Islam Nahdlatul Ulama Jepara, 2019)
The maternal health record is a record that contains the development of the fetus and the pregnant health record as well, this note is very important as a reference when a pregnant woman will give birth so that in addition to this note is given to the patient (pregnant women) midwife and gynecologist place control should also have this health record. Patients also often forget to bring even forget to put or keep this health notebook so forget the date of return control that has been written on the note note. Patients should not forget the date of re-control and not be empty of health record book then made the design of health information system for pregnant mother and mother-based sms notification with the aim can be a reminder of date of control visit for pregnant mother and reminded of date of estimated delivery. Methods of data collection is done by direct observation, interview and literature study. System design using UML modeling language. The result of this research is the design of information system of maternity health record and maternity based on sms notification with purpose as reminder of date of control visit for pregnant mother and reminder of estimated date of labor and assist in better management of maternal and maternal health record.